AFLP analysis reveals high genetic diversity but low population structure in Coccidioides posadasii isolates from Mexico and Argentina - Duarte-Escalante, Esperanza (2013)
Fil: Duarte-Escalante, Esperanza. Universidad Nacional Autónoma de México (UNAM). Facultad de Medicina. Departamento de Microbiología y Parasitología; México.